Advances in Numerical Simulation in Physics and Engineering Lecture Notes of the XV 'Jacques-Louis Lions' Spanish-French School - Parés, Carlos.; Parés, Carlos.; Vázquez, Carlos.; Vázquez, Carlos.; Coquel, Frédéric.; Coquel, Frédéric. (SEMA SIMAI Springer Series,, 2014)
This book, based on the lecture notes from the XVth Spanish-French School on Numerical Simulation in Physics and Engineering, covers a range of advances in numerical simulation in physics and engineering. The main subjects addressed are: biomechanics, stochastic calculus, geophysical flow simulation, and shock-capturing numerical methods for hyperbolic systems of partial differential equations. The book is mainly aimed at young graduate students in mathematics, engineering, and natural sciences who are starting to confront numerical simulation, either at a research level or in the field of industrial applications. It will also be helpful for researchers or even technicians who are working in an industrial environment and are interested in the state-of-the-art numerical techniques in these fields. Finally, the book will be useful as a textbook for master's or PhD level courses in mathematics, physics, or engineering.